A water-soluble small molecular fluorescent sensor based on phosphazene platform for selective detection of nitroaromatic compounds - Tumay, Suereyya Oguz; Senocak, Ahmet; cosut, Bunyemin; Alidagi, Huesniye Ardic; Yeşilot, Serkan (Springernature, 2023)
Nitro-aromatic compounds have a deleterious effect on the environment and they are extremely explosive. Therefore, societal concern about exposure to nitro-aromatic compounds encourages researchers to develop selective and sensitive detection platforms for nitro-aromatic compounds in recent years. In this paper, a new 100% water-soluble cyclotriphosphazene-based bridged naphthalene material (4) was prepared as a small molecule fluorescent sensor for ultra-selective detection of nitro-aromatic compounds. The chemical structure of 4 was extensively characterized by mass spectrometry and nuclear magnetic resonance spectroscopies (P-31, C-13, H-1). The photo-physical properties of the newly developed sensing system were investigated by steady-state fluorescence and UV-Vis absorption spectroscopies. The fluorescence sensor behaviors were extensively evaluated after treatment with the most commonly used metal cations, anions, competitive aromatic compounds, saccharides, and organic acids. The developed fluorescent sensing system (4) demonstrated ultra-selective fluorescence turn-off signal change toward nitro-aromatic compounds while other tested competitive species caused negligible changes. To evaluate selectivity, time-resolved, steady-state 3D-fluorescence and UV-Vis absorption spectroscopies were used in fully aqueous media. Moreover, theoretical calculations (density functional theory and time-dependent density functional theory) were applied and discussed to identify fluorescence sensing mechanisms toward nitroaromatic compounds for the presented sensing system.[Graphical Abstract]
Keywords: Intramolecular Excimer Formation; Resonance Energy-Transfer; Conjugated Polymer; Graphene Oxide; Tnt; Explosives; Naphthalene; Recognition; Framework; Solvent